2008
DOI: 10.1158/1078-0432.ccr-07-4489
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of the Tetraspanin CD9 during Disease Progression in Multiple Myeloma Cells and Correlation with Survival

Abstract: Purpose: The purpose of this study was to investigate expression and epigenetic regulation of CD9 in multiple myeloma (MM) cells during disease progression. Experimental Design: CD9 expression was retrospectively analyzed on bone marrow myeloma samples from 81 patients by immunophenotyping. CD9 expression by murine 5TMM cells was detected by flow cytometric staining and quantitative PCR. The methylation status of the CD9 promoter was determined by bisulfite PCR sequencing. Results: Primary plasma cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
1
33
1
2
Order By: Relevance
“…The similar observations were made in lung cancer and MMs. 48,60 Although it has recently been reported that mRNA modifications (i.e., deletion, insertion, or mutations) could play a role in regulating CD9 during prostate cancer progression, 47 we could not detect any deletion and insertion in CD9 mRNA when full length of coding region of CD9 was amplified. However, because the possibility precludes CD9 detection depending on epitopes recognized by CD9 antibody used for immunohistochemical staining, it should be taken into consideration.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The similar observations were made in lung cancer and MMs. 48,60 Although it has recently been reported that mRNA modifications (i.e., deletion, insertion, or mutations) could play a role in regulating CD9 during prostate cancer progression, 47 we could not detect any deletion and insertion in CD9 mRNA when full length of coding region of CD9 was amplified. However, because the possibility precludes CD9 detection depending on epitopes recognized by CD9 antibody used for immunohistochemical staining, it should be taken into consideration.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, CD9 expression has been reported to correlate with tumor progression in various tumors but has not been studied in B lymphomas. [43][44][45][46][47][48] CD9 is highly expressed on less aggressive L3055-12 but not on more aggressive L3055-33. pression upon transition of less aggressive B lymphomas to advanced B lymphomas appeared not to be limited to L3055 cells because CD9 expressing two other B lymphoma cell lines (i.e., Wan and BL40) also gradually lost CD9 after prolonged in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD9 also functions as a motility/migration brake (Ono et al, 1999), and this might explain the correlation detected between CD9 expression and the pattern of BM involvement. In multiple myelomas (MM), there is CD9 expression in non active MM, while in active and aggressive MM there is an epigenetic silencing of CD9 gene expression (De Bruyne et al, 2008).…”
Section: Tetraspanin Proteins In B-cell Malignanciesmentioning
confidence: 99%
“…Tetraspanins are a family of evolutionarily highly conserved proteins which influence a wide variety of physiologic processes and diseases, among others protein trafficking [Berditchevski and Odintsova, 2007], modulation of immune-signaling complexes [Levy and Shoham, 2005], and cancer [Z€ oller, 2009]. The regulated expression of TSPAN8 (also known as TM4SF3 or CO-029) is important for early development of the pancreas [Jarikji et al, 2009] and TSPAN8 protein abundance is known to be positively correlated with tumor progression , similar to tetraspanins CD151 (TSPAN24) [Yang et al, 2008] or TSPAN1 [Scholz et al, 2009] and opposite to, for example, CD9 (TSPAN29) [De Bruyne et al, 2008] or CD82 (TSPAN27) [Miranti, 2009], whose protein expression is negatively correlated with malignant phenotype. Besides the severe impact of expression changes of TSPAN8 and tetraspanins in general, mutations in TSPAN7 (CD231, TM4SF2) resulting in the amino acid substitution P172H lead to X-linked mental retardation [Zemni et al, 2000;Maranduba et al, 2004].…”
Section: à6mentioning
confidence: 99%